Pelayanan Administrasi Kepegawaian Dalam Meningkatkan Kinerja Pegawai Pada Kantor Kecamatan Tanjung Batu Kabupaten Ogan Ilir - suryani, riza adelia; Rifdi, Rama (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
The implementation of administrative services in an agency is much less relevant to what is expected so that the results obtained are also not in line with expectations. One of them is the Tanjung Batu District Head Office. The results of the author's initial observations at the Tanjung Batu District Head Office showed that the implementation of this administrative service was not in accordance with the expected goals. In this case the administrative unit must always be ready to provide accurate information services in solving administrative problems in general. To be able to carry out this administrative service task, employees who work in the administrative unit are not only supported by the willingness and work factor, but also must be equipped with special skills in the field of administration. This study uses qualitative methods, qualitative methods are a process of research and understanding based on a methodology that investigates a social phenomenon and human problem. The purpose of this study was to determine the administrative services of employees in improving employee performance at the sub-district office of Tanjung Batu. Based on the results of the research and interviews that have been described, it can be concluded that the Civil Service Administration Service in Improving Employee Performance at the Tanjung Batu District Head Office has been going well, this is because the services provided have not changed because they are in accordance with the main duties and SOPs that have been set.